Studi Mengenai Nilai Hematokrit Dan Jumlah Trombosit Dengan Kejadian Syok Dan Tipe Syok Pada Demam Berdarah Denguedi Rsud Abdul Wahab Sjahranie Samarinda - Rachmi, Rizma Alfiani; , Prof. Dr. dr. Bambang Subagyo, Sp. A (K); , dr. Yusuf Alam Romadhon, M.Kes (2015)
Background:Dengue Hemorrhagic Fever is one of the most common tropical diseases found in Indonesia. The fever attacks all ages, young and adult though it commonly found in young ages patients. The limited ability of hemodynamic system to compensate the capillaries leak in a child believed to be the lead of Dengue Shock Syndrome on children. Nevertheless, to define which case can be developed into shock on dengue hemorrhagic fever patients is hardly predictable. At such, laboratories findings covering hematocrit value and thrombocytes amount check is expected to anticipate the case of Dengue Shock Syndrome. Thus, an anticipated method can be executed to reduce the morbidity and mortality numbers in Dengue Hemorrhagic Fever patients. Objectives:This study aimed at finding the relevant between hematocrite value and thrombocytes amount as a risk factor of shock case in Dengue Hemorrhagic Fever patientsand the frequency distributed of shock case among Dengue Hemorrhagic Fever patients in General Hospital Abdul Wahab Sjahranie Samarinda. Methode :This study is analytical observation using cross sectional method. Result :Data studied on hematocrit value and thrombocytes amount on shock syndrome case founded in Dengue Fever patients in General Hospital Abdul Wahab Sjahranie Samarinda is examined by chi-square examination, founded in hematocrit value of p= 0.056 (p<0,05) which is statistically insignificant and in thrombocytes amount of p=0,000 (p<0,05) which is statistically significant. Conclusion:There is a significant correlation between thrombocytes amount and shock case on Dengue Hemorrhagic Fever patientsin General Hospital Abdul Wahab Sjahranie Samarinda whilst a significant correlation cannot be found between hematocrit value and shock case on Dengue Hemorrhagic fever patients in the same hospital.